2008
DOI: 10.1038/nbt1418
|View full text |Cite
|
Sign up to set email alerts
|

Induction of pluripotent stem cells by defined factors is greatly improved by small-molecule compounds

Abstract: Approach Summary Licensing status Publication and contact information Drug platforms Chemically mediated somatic cell reprogramming Cell-culture studies suggest that inhibitors of chromatin-modifying enzymes can increase the efficiency with which somatic cells are reprogrammed to pluripotent stem cells, providing a potential boon to the development of stem cell-based therapies. In mouse embryonic fibroblasts expressing four transcription factors (Oct4, Sox2, Klf4 and c-Myc) that are sufficient to induce plurip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
1,231
7
27

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,484 publications
(1,289 citation statements)
references
References 14 publications
24
1,231
7
27
Order By: Relevance
“…To this end, several inhibitors of DNA and histone methyltransferase, as well as histone deacetylase (HDAC) inhibitors have been found to dramatically improve reprogramming efficiency (Huangfu et al, 2008a;Shi et al, 2008).…”
Section: Change Of Epigenetic Landscapementioning
confidence: 99%
See 1 more Smart Citation
“…To this end, several inhibitors of DNA and histone methyltransferase, as well as histone deacetylase (HDAC) inhibitors have been found to dramatically improve reprogramming efficiency (Huangfu et al, 2008a;Shi et al, 2008).…”
Section: Change Of Epigenetic Landscapementioning
confidence: 99%
“…The first compounds used in reprogramming experiments were DNA methyltransferase inhibitor 5′-azacytidine and the HDAC inhibitor valproic acid (VPA), which increased the reprogramming efficiency by five fold and more than a hundred fold respectively (Huangfu et al, 2008a(Huangfu et al, , 2008bMikkelsen et al, 2008). Some small molecules could replace certain reprogramming factors.…”
Section: Chemical Compoundsmentioning
confidence: 99%
“…Barriers to this approach include the use of viral vectors and potentially oncogenic genes, as in the case of iPS [139]. The reprogramming potential of small molecules is already being investigated as an alternative [140,141].…”
Section: Differentiating the Renal Blastemamentioning
confidence: 99%
“…In addition, the viral vectors after integration with the host may lead to unexpected genetic disorder (Okita et al 2007;Takahashi et al 2007;Tateishi et al 2008;Yu et al 2009). Therefore, new and improved methods of generating iPS cells, including minimal or no genetic modification are needed (Huangfu et al 2008;Kaji et al 2009;Okita et al 2008;Stadtfeld et al 2008;Woltjen et al 2009;Yu et al 2009;Zhou et al 2009). Tateishi et al (2008) reported that iPS cells derived from human skin fibroblast by retroviral expression of OCT4, SOX2, c-MYC, and KLF4 have the potential to differentiate into insulin-producing islet-like clusters (ILCs).…”
Section: Differentiation Of Induced Pluripotent Stem Cellsmentioning
confidence: 99%